2012
DOI: 10.1501/egifak_0000001240
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the effect of social stories in teaching of social skills to children with autism

Abstract: ABSTRACT. The aim of this study is to help a child with autism in an inclusive preschool programme to introduce herself, to ask for help or information and to acquire skills to participate in daily activities through social stories. In this study, one of the single subject methods called multiple probe model with probe condition across behaviors is used. In order to teach social skills such as introducing herself, asking for help or information and participate in daily activities, social stories are written an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
(15 reference statements)
2
3
0
2
Order By: Relevance
“…Results obtained with graphical analysis demonstrated that SS were effective in children with ASD to achieve, generalize, and retain target social skills one, three, and five weeks after the instruction was terminated. This study's results are consistent with the results of other studies conducted on social skills instruction to children with ASD (Acar et al, 2016;Adams et al, 2004;Balçık & Tekinarslan, 2012;Bernad-Ripoll, 2007;Kuoch & Mirenda, 2003;Olçay-Gül & Tekin-İftar, 2016;Quilty, 2007;Xin & Sutman, 2011). The most significant characteristic that differentiates the present study from others is the fact that SS were designed and applied by PST.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Results obtained with graphical analysis demonstrated that SS were effective in children with ASD to achieve, generalize, and retain target social skills one, three, and five weeks after the instruction was terminated. This study's results are consistent with the results of other studies conducted on social skills instruction to children with ASD (Acar et al, 2016;Adams et al, 2004;Balçık & Tekinarslan, 2012;Bernad-Ripoll, 2007;Kuoch & Mirenda, 2003;Olçay-Gül & Tekin-İftar, 2016;Quilty, 2007;Xin & Sutman, 2011). The most significant characteristic that differentiates the present study from others is the fact that SS were designed and applied by PST.…”
Section: Discussionsupporting
confidence: 91%
“…It was determined in the maintenance sessions that the children maintained their acquired skills at the accuracy rate of 100%. This supports the results obtained from other SS studies in the literature (Acar et al, 2016;Balçık & Tekinarslan, 2012;Crozier & Tincani, 2007;Leaf et al, 2012;Olçay-Gül & Tekin-İftar, 2016;Sansosti & Powell-Smith, 2008;Schneider & Goldstein, 2010;Theiman & Goldstein, 2001;Thompson & Johnston, 2013;Turhan & Vuran, 2015;Quilty, 2007). Generalization data were collected from both children with ASD and PST.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…They are either directly read by the child or someone reads them to the child; then the child is expected to perform the behavior in a related social context. SS have been used for teaching social interaction and communication skills (Adams, Gouvousis, VanLue, & Waldron, 2004; Balcik & Tekinarslan, 2012; Delano & Snell, 2006; Hanley-Hochdorfer, Bray, Thomas, Kehle, & Elinoff, 2010; Olçay-Gül & Tekin-Iftar, 2016; Sansosti, Powell-Smith, & Kincaid, 2004; Scattone, Tingstrom, & Wilczynski, 2006; Thiemann & Goldstein, 2001), safety skills (Suzer, 2015), and play skills (Barry & Burlew, 2004; Kourassanis, Jones, & Fienup, 2015) to individuals with autism across various age groups.…”
mentioning
confidence: 99%
“…Findings of a single subject research revealed that social stories increased prosocial behaviors in four preschool children with ASD (Wright & McCathren, 2012). The results of another single-subject study by Balçık and Tekinarslan (2012) showed that social stories were effective in gaining the ability to introduce themselves, ask for help and participate in daily activities in a four-year-old child with ASD. Findings of another single subject study demonstrated effectiveness of Power Card Strategy, a story based intervention, in teaching appropriate social skills on the playgrounds for a five years old child with ASD (Spencer, Simpson, Day, & Buster, 2008).…”
Section: Story-based Interventionsmentioning
confidence: 95%